Glass Elevator at Kelingking Beach: A Comparative SWOT Analysis of Infrastructural Innovations in Tourist Destinations - Suhardono, Sapta; Suryawan, I Wayan Koko (Lasigo Akademia Indonesia, 2024)
This study undertakes a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis of the proposed glass elevator installation at Kelingking Beach, a renowned tourist destination in Bali. The research draws upon diverse scholarly perspectives to offer a comparative lens on infrastructural developments in natural settings. While the glass elevator promises to democratize access, particularly for older people and those with mobility challenges, and possibly amplify economic gains, it also brings forth concerns related to overdevelopment, environmental impact, and the risk of compromising the intrinsic charm of the destination. Our findings elucidate that while there are clear strengths, such as enhanced accessibility and potential for premium pricing, there are notable challenges to consider. The weaknesses, primarily arising from potential safety concerns and the possibility of detracting from the beach's natural allure, call for thoughtful solutions. Opportunities present themselves through collaborative efforts, sustainable practices, and a reinvigorated tourism sector. The study serves as a template for policymakers and stakeholders in natural tourist destinations, aiming to integrate infrastructure without diluting the essence of the locale.